Karl Holl (1866-1926) – luterański badacz źródeł patrystycznych - Widok, Norbert (Vox Patrum, 2019)
The content of this article was devoted to the researcher of Christian antiquity, Karl Holl (1866-1926), who lived in the late nineteenth and early twentieth century. Born into a Protestant family, he was deeply involved in the deepening and development of Protestantism in Germany with both socio-religious and literary activity. In addition to this range of activities in his life, he also turned out to be an outstanding historian, also publishing scientific contributions relating to Christian antiquity. Of these, critical editions including Epiphanius writings deserve special mention. He boldly presented his point of view regarding the authorship of works depicting Epiphanius as iconoclast, and being attributed to other authors for centuries. Despite the extensive discussion lasting several decades in the 20th century, the research line outlined by K. Holl remained unchanged. The research proficiency and reliability in conducting philological and historical analyzes of this scholar therefore deserve recollection. Key words: Karl Holl, historian, Early Christian literaturę, critical editions, Protestantism.